Características clínico-epidemiológicas y laboratoriales de dengue en gestantes en un hospital público de Loreto, durante el año 2022 - Taminche Canayo, Ruth Cecilia (2023)
Objectives: The general objective was to determine the clinical-epidemiological and laboratory characteristics of dengue in pregnant women in a public hospital in Loreto, during the year 2022. Materials and methods: A descriptive, cross-sectional, observational study included 108 pregnant women with a presumptive diagnosis of dengue from the Gynecology and Obstetrics area of the Hospital Iquitos César Garayar García from January to December 2022. A collection instrument validated by experts was used, obtaining the information from medical records. An observational, descriptive, cross-sectional analysis was carried out to determine the clinical-epidemiological and laboratory characteristics of dengue in pregnant women. Results: The prevailing age ranged from 20-34 years, most of them finished high school, are cohabiting and independent (housewives). The largest number of pregnant women come from urban areas, from the district of Belén, and the majority of their nutritional status is overweight. They had no history of dengue (98.1%). In the gynecologic and obstetric history, the majority were affected in the third trimester, but there was a greater number of admissions in preterm pregnant women, the pregnant women were more primiparous, the majority did not have abortions, and more than half were adequately controlled. The largest number of concomitant diseases in pregnant women were different from diabetes and hypertension. More pregnant women were hospitalized from 1 to 5 days, more than half had a cesarean section. There were 12 positive patients for NS1, but 72 for clinical, 46 for laboratory and 31 for both. Both hemoglobin and hematocrit were related in all pregnant women, without having high amounts, platelets, in most patients, had a normal value, leukocytes, in half, maintained a low value. Conclusions: There was a relationship between the clinical and epidemiological characteristics and the laboratory findings. Likewise, the most frequent warning signs were abdominal pain, vomiting and nausea. The most frequent maternal complications were anemia and hemorrhage.